Intelligent automation for successful processes: n8n as a driver of digital efficiency - Moreno, Mario S. (2025)
In a context where digital systems are becoming increasingly fragmented, process integration and automation are no longer a technical luxury, but a structural necessity for scaling, protecting data, and improving the end-user experience. This paper analyzes the strategic potential of n8n, an open-source automation and integration platform that combines the best of a low-code approach with the extensibility of traditional development. Through a technical and functional comparison with other market-leading tools such as Zapier and Make, it argues why n8n, especially its Community Edition, represents an ideal solution for software development companies seeking flexibility, control over their workflows, and technological sovereignty. It also explores its API integration capabilities, its modular architecture, and its native support for AI. It also presents real-world application cases in workflows such as automated onboarding, ETL, continuous testing, and omnichannel support. Finally, the importance of adopting a collaborative approach between automation and development is discussed, overcoming the false dilemma between "low-code vs. high-code" and proposing a synergy that fosters secure, scalable, and sustainable digital products.